Physical Principles of Elastography: A Primer for Radiologists - Patra, Sayantan; Grover, Shabnam Bhandari (Indographics, 2022)
Elastography is the noninvasive method of qualitative and quantitative evaluation of strain and elastic modulus distribution in soft tissues. In simpler terms, elastography is the science of measuring tissue stiffness, the deviation of which correlates with pathology of the tissue/organs being evaluated. Whereas, elasticity, refers to the property of solid matter to return to their original shape and size after removal of the deforming forces. In all forms of elastography, irrespective of the types of deforming forces or moduli, the deformation of tissue occurs in the form of shear deformation. The velocity of shear waves in the deformed tissue depends on its density and on the shear modulus. The direction of propagation of shear wave is perpendicular to the inciting mechanical or acoustic wave. The shear wave is then subsequently tracked using multiple tracking pulses, which measures tissue displacement in response to the passing shear wave. The calculated speed of the shear wave is then converted to conventional Young's modulus for the purpose of computing the tissue stiffness.The currently used elastography techniques are static or quasi-static elastography and dynamic elastography. Strain elastography (a form of static or quasi-static elastography) is based on the principle of acquisition of radio-frequency (RF) signals before and after the application of a deforming force in the form of slight compression of tissue by a transducer. RF signals are compared between the pre-compression image data set and the post-compression image data set and correlated between the two data sets.Dynamic elastography may be either ultrasound (US) based or magnetic resonance (MR) based. The types of dynamic US elastography are: acoustic radiation force impulse imaging (ARFI), transient elastography (TE), point shear wave elastography (pSWE), and shear wave elastography (SWE). ARFI uses a standard transducer to produce and propagate rapid bursts of long focused ultrasound pulses, also called as “push pulses” which cause tissue deformity, the propagation of which is tracked using radio-frequency echo tracking. In TE, a probe mounted on a vibrator is used to produce a small thump by piston like motion of transducer. The shear wave which arises from the edges of the transducer is tracked using high pulse repetition frequency tissue Doppler and computed using M-mode for display of quantitative parameters. Point shear wave, also known as quantitative ARFI, uses shear waves generated using transient tissue displacement caused by ARFI and are subsequently subjected to tracking by Doppler. Shear wave elastography is based on the principles of imaging shear wave speed. An acoustic radiation force impulse is transmitted along the acoustic axis to produce tissue displacement and deformation at points of acoustic axis. The generated shear wave is imaged using RF echo tracking over a grid of points, which is translated into a real time image. MR elastography is a dynamic technique and the basic principles of MR elastography are the same as other forms of dynamic elastography. MR elastography has limited utility in iron-overload states and in addition, due to the large amount of time required for acquisition, the technique is not suitable for unstable patients.This review presents a simplified summary of the principles of elastography along with definition of the terms and the types of elastography which are currently available to radiologists for clinical application and concludes with a brief on the newer developments for the future.
Keywords: elastography; strain elastography; ARFI; transient elastography; point Shear wave elastography; shear wave elastography; MR elastography